Risk assessment for type 2 diabetes mellitus in the municipality of Golubac - Trifunović, Boban; Fišeković Kremić, Marina (General Practice, 2023)
Introduction. There are approximately 17.000 new cases of diabetes mellitus type 2 (DM2) in Serbia each year. A third of the newly diagnosed already has some late disease complications and almost half of them are over 65. Objective. We aimed at determining the level and risk factors for DM2 in respondents of different gender, age, and lifestyle in the Municipality of Golubac. Method. The study was conducted using the DM2 questionnaire. The sample had 404 participants who were screened in the Municipality of Golubac. Significant statistical methods were used in the study: frequency, t-test, ANOVA test, and correlation analysis. Results. The study showed the majority of participants (40.1%) had slightly elevated risk for DM2, high risk was found in 14.9%, and very high risk in 3.2%. Moderate risk was found in 27.5% of the participants and 14.4% had low risk. Women had a higher percentage of high and very high risk for DM2 than men but no statistically significant difference was found between men and women concerning the risk of developing the disease. With age, as well as obesity, the risk for DM2 increases. The participants who practiced regular physical activity, as well as those who regularly consumed fruits and vegetables, had a lower risk for DM2. Conclusion. The study showed almost every fifth participant had a high or very high risk for DM2, 81.7% were overweight, and 75% had previously diagnosed cardiovascular problems. Registration of persons with an elevated risk for DM2 and further follow-up is a very important task for GPs (general practitioners). Keywords: diabetes, screening, risk factors, obesity